IDENTIFICATION AND TAXONOMIC ANALYSIS OF VARIOUS INSECTS IN THE WONOREJO MANGROVE TOURISM AREA IN SURABAYA - Maulana, Fauzan (Journal of Natural Sciences and Learning, 2025)
The Wonorejo Surabaya Mangrove Tourism Area, one of the largest mangrove ecosystems in East Java, significantly contributes to biodiversity, particularly insect communities. This study aims to identify and analyse the taxonomy of various insect species inhabiting the region. A three-week field study was conducted in December 2024 using the sweep net method. Taxonomic analysis employed Linnaeus’ classification, while species identification relied on identification keys and relevant literature. The study revealed 15 insect species, including Pantala flavescens, Acisoma panorpoides, Danaus chrypsippus, Junonia orithya, Balenois aurota, Appias olferna, Junonia coenia, Catopsilia pyranthe, Eurema blanda, Catopsilia pamona, Xylocopa latipes, Papilio demodocus, Junonia almana, Hypolimnas bolina, and Vespa affinis. These species span three orders (Odonata, Lepidoptera, Hymenoptera), six families (Libellulidae, Nymphalidae, Pieridae, Apidae, Papilionidae, Vespidae), and 12 genera  (Pantala, Acisoma, Danaus, Junonia, Balenois, Appias, Catopsilia, Eurema, Xylocopa, Papilio, Hypolimnas, Vespa). This study highlights exceptional biodiversity and significant genetic potential for mangrove habitat conservation. These findings are crucial for regional management and conservation, including habitat protection and environmental education. Further research is necessary to understand insect ecological roles and develop effective conservation strategies for maintaining the health of Wonorejo’s mangrove ecosystem.